Multiple Lower Eyelid Nodules In Breast Cancer Patient With History Of Dermal Fillers: A Case Report - Gunardi, Alberta Jesslyn; Marsaulina, Renate Parlene; Kevin, Jonathan; Sakura, Irena (Jurnal Plastik Rekonstruksi, 2019)
Background: Dermal filler injections have been associated with several complications, including migration to other areas and forming nodules due to the presence of foreign bodies or granulomatous reactions may develop, which encapsulates the filler. Fillers might also be associated with malignancy. The presence of such complications must be removed with reconstructive surgery. Methods: We present a case of breast cancer patient with a history of dermal filler injection to the lower eyelid. The nodules in the lower eyelid was surgically removed, and the lower eyelid, particularly the muscle, was reconstructed to provide a good cosmetic result. The nodules were also pathologically examined to confirm the diagnosis. Reconstruction of the lower eyelid was conducted with care by noting the aesthetic aspects. Results: A local muscle flap was easy to harvest and handle, and provided good results. It is also important to consider malignancy to treat the patient thoroughly. The pathology examination confirmed the diagnosis of metastasis. This case is unique because the nodules developed in the patient may be associated with metastasis of the cancer or the dermal filler injection. Conclusion: Our reconstruction technique leads to a good cosmetic result. There are no sign of complications and recurrence at 3 months following the procedure.